Статистичні дані про етнічний, соціальний, кількісний склад учнів Чернігівської класичної чоловічої гімназії у XІX столітті - Рига, Д. (Сiверянський лiтопис, 2017)
У статті подаються статистичні дані про етнічний, соціальний, кількісний склад
учнів Чернігівської класичної чоловічої гімназії у XІX столітті. В статье подаются статистические данные об этническом, социальном, количественном составе учащихся Черниговской классической мужской гимназии в XІX веке. The nationality of the pupils of the gymnasium was different, but it depended directly on
the nationalities of the inhabitants of the city of Chernigov in this historical time. According
to the documents on the activities of the gymnasium, here mainly studied: Ukrainians, Jews,
Russians. Students from different parts of society studied in the high school, but mostly they
were children from aristocratic families.
Throughout the first half of the XIX century, children from aristocratic families prevailed,
second came from families of officials, in third place came from the families of brothels, the
fourth came from families of merchants, the fifth native of the families of the clergy, and
in sixth place, according to the number of pupils, came from families of state peasants. The
number of students in the gymnasium gradually increased, as in the year 1810, it was equal
to 73 people; in 1843, 350 students attended the gymnasium.
The increase in the buildings of the gymnasium was necessary because the number of
people who wanted to study at an institution grew rapidly. The guesthouse or foreign students’
boarding house was built in 1850 at the Chernihiv Men’s Gymnasium and during the XIX -
early XX centuries, it actually served as a “hostel» for high school students.
The conduct of the students of the gymnasium did not bear any kind of political deviation
from the norm, although there were acts that entailed not only short-term arrest but also
dismissal without the right to enter other educational institutions. These included: theft on the
market, livelihood for teachers, and the consumption of alcoholic beverages.
Activities of the Chernigov classical male gymnasium, throughout the XIX century, were
characterized as very well organized. Students who studied at the gymnasium received a
fairly profound secondary education, as evidenced by the volume of the curriculum of the gymnasium lessons.